DIALOGUE JOURNALS IN IMPROVING STUDENTS’ WRITING DESCRIPTIVE TEXT - Yunda Lestari (Journal of English Education, Literature and Linguistics, 2018)
This study aimed to find out whether there is significant improvement of students’ writing ability through dialogue journal to the eleventh grade students of SMA Kurnia Jaya in the Academic Year 2017/2018. The population of this study was the eleventh grade students of SMA Kurnia Jaya in the Academic Year 2017/2018. The total number of the population was 78 students from three classes. Pre-experimental method was used in this study and cluster random sampling was used in taking the samples. Class XI. IPA was taken as sample which consisted of 25 students. Based on the result of the test, the writer found that the students’ mean score in the pre-test was 41,17 while in the post-test was 59,17 Based on the table, it was shown that the value of t-obtained was 8,630, in two tailed testing with df = 24, the critical of t-table was 1.711. Since the value of t-obtained was higher than the critical value of t-table, it meant that there was a significant difference in achievement before and after the treatment. Since the value t-obtained was higher than t-table (9,605>1.711), so the null hypothesis (Ho) unacceptable and the alternative hypothesis (Ha) of this research was accepted.